2018
DOI: 10.1186/s12889-018-5997-1
|View full text |Cite
|
Sign up to set email alerts
|

Character strengths as protective factors against depression and suicidality among male and female employees

Abstract: BackgroundSo far, studies on workplace mental health have only focused on work-related environmental risk factors, disregarding both protective and individual factors of employees. Therefore, we aimed to identify character strengths that act as protective factors against depressive moods and suicidality in Korean employees.MethodsIn total, 84 male and 151 female employees (aged 19–50 years) reported their sociodemographic characteristics; depressive symptoms, as measured by the Beck Depression Inventory-II; su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
2
19
1
3
Order By: Relevance
“…This factor includes items such as, “There is at least one person who is close and able to help me when I am stressed,” and “I know who to ask for help in a stressful/crisis situation.” A previous study conducted with radiologists reported social support to be a protective factor against depressive mood and anxiety 30. In a previous study of character strengths, “judgement” and “kindness” in women and “teamwork” and “creativity” in men were protective factors against depression and suicidality among employees 31. In addition, strengths related to social support, including “kindness,” “teamwork,” and “humor,” were associated with decreased negative coping among employees in various types of jobs 32.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This factor includes items such as, “There is at least one person who is close and able to help me when I am stressed,” and “I know who to ask for help in a stressful/crisis situation.” A previous study conducted with radiologists reported social support to be a protective factor against depressive mood and anxiety 30. In a previous study of character strengths, “judgement” and “kindness” in women and “teamwork” and “creativity” in men were protective factors against depression and suicidality among employees 31. In addition, strengths related to social support, including “kindness,” “teamwork,” and “humor,” were associated with decreased negative coping among employees in various types of jobs 32.…”
Section: Discussionmentioning
confidence: 91%
“…A problem-focused approach involves analyzing the problem in detail and adjusting or eliminating problems that cause stress. In a previous study, “judgement” was reported to be a protective character strength against suicidality in women workers 31. “Judgment,” representing intellectual ability, plays an important role in selecting adaptive coping skills and avoiding maladaptive coping skills in the workplace 32.…”
Section: Discussionmentioning
confidence: 97%
“…To operationalize character, Peterson and Seligman proposed a “Value in Action” (VIA) model with 24 character strengths categorized into six dimensions, including “wisdom and knowledge”, “courage”, “humanity”, “justice”, “temperance” and “transcendence” 57,58. Scientific research showed that character strengths were not only strong buffers against a variety of adolescent psychosocial problems such as internalizing and externalizing problems, depression and suicidality,5961 but also positively associated with life satisfaction, well-being, happiness and academic achievements 62–64. According to Battistich, character emphasizes the commitment to contribute to one’s community 65.…”
Section: Pyd Models and Approachesmentioning
confidence: 99%
“…Employing the VIA-Youth, empirical studies have found that character strengths could promote positive behavioral, mental, and emotional developmental outcomes in adolescents ( Datu & Mateo, 2020 ; Shoshani & Slone, 2013 ; Wagner, 2019 ; Weber & Ruch, 2012 ). With regard to depression symptoms, some character strengths were found to be inversely related to individual depression symptoms ( Kim et al, 2018 ; Tehranchi et al, 2018 ). In addition, prior work has indicated that interventions targeting character strengths can reduce depression symptoms in adults ( Schutte & Malouff, 2019 ).…”
Section: Introductionmentioning
confidence: 99%